What Factors Attract Venture Capital And Angel Investor Funding: Case Of Indonesia - Esa, Abrori Ahmad Noor; Nainggolan, Yunieta Anny (Journal Integration of Social Studies and Business Development, 2023)
This research aims to understand the factors that influence venture capital investment decisions in startups and create a model for making these decisions. The Analytic Hierarchy Process method gathered data from venture capitalists and investors. To design a decision-making concept model, this study examined various factors considered in venture capital and investors' decision on an investment based on previous significant studies. It employed 16 evaluation items centered on four areas —entrepreneur, product and service, market, and finance. The results concluded that the product/service sector was the most important area, with the product's value being the most important factor. Business compatibility is the second most important factor, followed by the entrepreneur sector. This research conducted a survey based on a sample from Indonesia. The conclusion of this study is expected to help venture capitalists and investors better judge startup funding.